2019
DOI: 10.1515/htmp-2019-0005
|View full text |Cite
|
Sign up to set email alerts
|

Controlling residual stress and distortion of friction stir welding joint by external stationary shoulder

Abstract: Friction stir welding (FSW) can achieve a sound welding joint, but its residual stress and distortion cannot be avoided due to the non-uniformity of temperature distribution during welding. Stationary shoulder friction stir welding (SSFSW) was employed to butt weld 6005A-T6 aluminum alloy plates. The effects of welding speeds ranging from 200 mm/min to 600 mm/min on residual stress and distortion were investigated in detail. A thermo-mechanical model was utilized to compare the residual stress distribution bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Hence, a narrower NZ and tensile region are obtained. Recent studies [25][26][27] reported promising results regarding the capability of SSFSW as an in-situation mitigation technique. As compared to other techniques, SSFSW does not require expensive apparatus, making it practical for both research and industrial applications.…”
Section: Stationary Shoulder Friction Stir Weldingmentioning
confidence: 99%
“…Hence, a narrower NZ and tensile region are obtained. Recent studies [25][26][27] reported promising results regarding the capability of SSFSW as an in-situation mitigation technique. As compared to other techniques, SSFSW does not require expensive apparatus, making it practical for both research and industrial applications.…”
Section: Stationary Shoulder Friction Stir Weldingmentioning
confidence: 99%
“…The major limitation of the previous techniques is the added cost of special equipment. To avoid the additional expense, stationary shoulder friction stir welding is a promising distortion‐control technique, according to recent studies 60,61 …”
Section: Propertiesmentioning
confidence: 99%
“…Generally, both increasing welding velocity and additional cooling give positive effects in terms of microstructure but, on the other hand, also increase residual stresses in welded elements [ 20 , 21 , 24 ]. Analyzing the used welding velocities, in many cases, the lowest value is 80 mm/min and the tool rotation speed exceeds 800 rpm [ 16 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, both increasing welding velocity and additional cooling give positive effects in terms of microstructure but, on the other hand, also increase residual stresses in welded elements [ 20 , 21 , 24 ]. Analyzing the used welding velocities, in many cases, the lowest value is 80 mm/min and the tool rotation speed exceeds 800 rpm [ 16 , 24 ]. Moreover, many investigations focus mainly on microstructural aspects (the evolutions of the strengthening phase, participation of grain boundaries in each welded zone), simultaneously failing to provide the mechanical properties data in a broad range of welding parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation